ANALISIS DAN IMPLEMENTASI APLIKASI PENERJEMAH DAN PENAMBAH HARAKAT KITAB KLASIK/KITAB KUNING - Aulia Faqih Rifa’i (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
This study aims to implement a translator and enhancer applications vowel in learning the classics / yellow bible and do analysis if the application is feasible and can be used to meet the users as well as in accordance with Islamic Schools learning model. This study uses the SDLC (System Development Life Cycle) that steps are requirements analysis, system design, system development, implementation and testing as well as analysis of the implementation. In making this application was built on the Android 2.3 platform with Tesseract OCR Engine and Tesstwo library and use a Java IDE and Eclipse ADT. In this study concluded that the application can recognize 90.3% of the Arabic alphabet, especially yellow bible of book of prints for the 65.17% level of user satisfaction.